Violencia intrafamiliar y su relación con el consumo de alcohol en adolescentes de 15 a 18 años del colegio Nacional Nocturno Manuel Enrique Rengel, año lectivo 2013-2014 - Celly Alvarado, Santiago José (2014)
Family violence is a social phenomenon that unfortunately at present is increasing, therefore this research has the overall aim to establish the relationship between family violence and consume of alcohol among teens from 15 to 18 years old of the Colegio Nacional Nocturno Manuel Enrique Rengel, school year 2013 – 2014. The present study is analytic, cross-sectional, which was developed in teens from 15 to 18 years old of the Colegio Nacional Nocturno “Manuel Enrique Rengel" at Loja city, where 136 teens were assessed. To perform data collection a survey was developed in order to know the demographic information of the sample: gender, age and what kind of family the teen belongs; was also inquired if the teen consume alcohol, if alcohol consume has caused violence and what kind of violence has occurred. As main result was obtained that family violence occurs by the family to the teenager displayed in 51.1%; while the violence produced by the teen to his family is 53.4%; happening "rarely" in both cases; the main kind of violence that occurs is "emotional or psychological" violence in 45.6% and 43.6% respectively for the cases. This way can be clearly establish and confirm the existence of the relationship between family violence as a result of alcohol consumption by adolescents. Keywords: domestic violence, alcohol consume, teenagers, kind of violence.